2007
DOI: 10.1111/j.1537-2995.2007.01571.x
|View full text |Cite
|
Sign up to set email alerts
|

Selection of hematopoietic stem cells with a combination of galactose‐bound vinyl polymer and soybean agglutinin, a galactose‐specific lectin

Abstract: SBA binds selectively to blood cells by recognizing cell-surface sugars, which are dependent on the extent of cellular differentiation. Therefore, the combination of alpha-1,6-Gal-VP and SBA might be useful for separation of blood cells according to their stage of differentiation and lineage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…30,31 The ability to recognize distinct carbohydrate determinants turned certain plant lectins into very valuable tools in blood typing, in evaluating cell differentiation processes, as cell separation and characterization agents, as markers used in microarrays, in immunological studies, and in studies of cell-cell recognition and cell signaling processes. [32][33][34][35][36] The importance of glycans in cell therapy has been known since 1988, when Hardy and Tavassoli showed that the carbohydrate moieties present on the stromal cells were important in homing stem cells bearing the corresponding lectin-like molecules and membrane lectins on a stem cell surface with a specificity for galactose and/or mannose-bearing glycoconjugates involved in the successful engraftment of hemopoietic progenitor cells in their specific stromal microenvironment. 37 Similarly, Hinge et al showed that the mannose-containing carbohydrate moieties present on the hematopoietic stem and progenitor cells were recognized by mannose-binding lectins and played an importantrole in the HSPC-protecting effect of these lectins.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 The ability to recognize distinct carbohydrate determinants turned certain plant lectins into very valuable tools in blood typing, in evaluating cell differentiation processes, as cell separation and characterization agents, as markers used in microarrays, in immunological studies, and in studies of cell-cell recognition and cell signaling processes. [32][33][34][35][36] The importance of glycans in cell therapy has been known since 1988, when Hardy and Tavassoli showed that the carbohydrate moieties present on the stromal cells were important in homing stem cells bearing the corresponding lectin-like molecules and membrane lectins on a stem cell surface with a specificity for galactose and/or mannose-bearing glycoconjugates involved in the successful engraftment of hemopoietic progenitor cells in their specific stromal microenvironment. 37 Similarly, Hinge et al showed that the mannose-containing carbohydrate moieties present on the hematopoietic stem and progenitor cells were recognized by mannose-binding lectins and played an importantrole in the HSPC-protecting effect of these lectins.…”
Section: Discussionmentioning
confidence: 99%
“…Both methods rely on recognizing target cells by antigen–antibody reactions using monoclonal antibodies, so these techniques are limited by the lack of specificity of the cell surface markers for which antibodies are available, as the markers are also expressed by significant subpopulations of maternal blood cells. LBEI is based on the observation that erythroid precursors show high surface expression of galactose molecules and it can be used to sort a larger number of erythroblasts compared with other technologies. However, LBEI is time‐consuming and also has the disadvantage of resulting in co‐isolation of a large number of non‐nucleated erythrocytes and leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“…SBA has served as an excellent system of choice to study the fundamentals of protein – carbohydrate interaction (Loris et al 1998 ; Sharon and Lis 1990 ). With a vast increase in knowledge of SBA and other lectins, it has become apparent that SBA has many additional applications, especially in medical and biotechnology-focused industrial areas such as the utilization of SBA to selectively remove cancerous cells from whole blood without removing normal T cells, to prevent graft-versus-host disease following transplant, or to enrich hematopoietic stem cells (Bakalova and Ohba 2003 ; Kernan et al 1987 ; Yura et al 2008 ). Moreover, recombinant SBA has the potential to serve as a carrier system for oral drug delivery or to be used as an affinity tag for isolation of high-purity fusion proteins.…”
Section: Discussionmentioning
confidence: 99%
“…One such application is the separation of pluripotent stem cells from human bone marrow. Cells fractionated by SBA do not produce graft versus host disease (GVHD) and can be used in bone marrow transplantation across histocompatibility barriers (Yura et al 2008 ). Another application is the enrichment and isolation of fetal cells from the blood of pregnant women as a means of detecting fetal genetic and chromosomal abnormalities.…”
Section: Introductionmentioning
confidence: 99%